If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2f + -4) = -4 + -1f + 2 Reorder the terms: -1(-4 + 2f) = -4 + -1f + 2 (-4 * -1 + 2f * -1) = -4 + -1f + 2 (4 + -2f) = -4 + -1f + 2 Reorder the terms: 4 + -2f = -4 + 2 + -1f Combine like terms: -4 + 2 = -2 4 + -2f = -2 + -1f Solving 4 + -2f = -2 + -1f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add 'f' to each side of the equation. 4 + -2f + f = -2 + -1f + f Combine like terms: -2f + f = -1f 4 + -1f = -2 + -1f + f Combine like terms: -1f + f = 0 4 + -1f = -2 + 0 4 + -1f = -2 Add '-4' to each side of the equation. 4 + -4 + -1f = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -1f = -2 + -4 -1f = -2 + -4 Combine like terms: -2 + -4 = -6 -1f = -6 Divide each side by '-1'. f = 6 Simplifying f = 6
| 3z+5+2z=13+3z | | =3(x+y)+4(y+x) | | 14+3n=8n-3+10x | | 2x^2+12+9x-18-3x-4x=0 | | x+x+1+x+2=-3.75 | | 11+3x-7=6x+-3x | | 9w-18w-18w+36= | | =6+6(x+4)+15y+x | | -1(x+4)+5=4x+1-5x | | 14+4x+6=8x | | -19x+23y=-3 | | 3x+14x+2=19 | | -4p+15=-15 | | =5(x+3)+3(y+1) | | 5x-3(x-4)=-5+4x+13 | | (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 |